Лінгвокультурема "пісня" в поетичному дискурсі Лесі Українки - Голікова, Н. (Культура слова, 2020)
У статті досліджено функціонально-стилістичні особливості лінгвокультуреми «пісня» в ідіолекті Лесі Українки. Простежено семантичну структуру ключового слова в мові різножанрових художніх творів мисткині, обґрунтовано специфіку його символьних значень. Визначено лексико-тематичні лінії з лінгводомінантою «пісня», що забезпечують змістову зв’язність поезій у вертикальному контексті мовотворчості Лесі Українки. Структуровано й описано семантико-асоціативне поле, осереддям якого є лексема «пісня» та дериваційно споріднені з нею слововживання. Лінгвокультурему «пісня» проаналізовано як один із найважливіших текстоцентричних компонентів лінгвокогнітивного простору авторської поезії та драматургії, що відбиває основні принципи організації національно- культурного універсуму загалом і його пісенно-музичної сфери зокрема. The article examines the functional and stylistic features of the linguocultureme of “song” in the idiolect of Lesia Ukrainka. It is emphasized that in the analyzed poetic discourse the word “song” is a key, stylistically marked component, which testifies to the relevance of semantics in the field of Ukrainian song and music culture. The branched semantic structure of the keyword in the language of various genres of poetic works of the writer, which consists of common and contextually determined lexical-semantic variants, is traced. The specificity of the symbolic meanings of the keyword “song” is substantiated, the basis for which are often folk poetic sources. Lexical-thematic lines with a dominant “song” are determined, which provide semantic coherence of poems in the vertical context of Lesia Ukrainka’s language creation. Among the main representatives of the textual integrity of the studied poetic and dramatic works such semantic-thematic oppositions and associative convergences as: “word” – “music” are actualized; “will” – “bondage”; “native land” – “foreign land”; “word”, “poetry”, “creativity”; “song”, “thought”; “brotherhood”, “equality”, “will”; “optimism”, “hope”; “song”, “dream”, “fantasy”, “dream”, etc. The semantic-associative field is structured and described, the center of which is the token “song” and derivations related to it. Linguocultureme «song» is analyzed as one of the key tectocentric components of the linguocognitive space of language creation of Lesia Ukrainka, which reflects the basic principles of organization of the national linguistic and cultural universe in general and its verbal and musical sphere in particular.